Hostage Taking (Gijzeling) in Tax Law Tax: A Perspective on the Protection of State Interests - Ikbal, Moh; A'la, Nurul (Universitas Negeri Gorontalo, 2025)
Gijzeling or detention in Indonesian tax law is an instrument used to ensure compliance with tax obligations by Taxpayers who have not settled their tax debts. Based on Law of the Republic of Indonesia Number 6 of 1983 concerning General Provisions and Tax Procedures, which was amended by Law Number 28 of 2007, gijzeling is applied when a Taxpayer has tax debt of at least Rp100 million and fails to meet the payment obligation after collection efforts have been made. This study aims to analyze the procedure and implementation of gijzeling in Indonesian tax law, as well as to evaluate the legal basis for the use of this instrument, including the procedures that must be followed to avoid violating the Taxpayer's rights. The methodology used in this study is a qualitative approach with normative legal research, which focuses on the analysis of applicable regulations, legal doctrines, and the practice of implementing gijzeling. The primary data sources come from relevant regulations, particularly the Tax Law and Director General of Tax Regulation Number PER-29/PJ/2015. The research findings indicate that while gijzeling is a valid instrument in enforcing tax law, its implementation must follow clear and fair procedures. Strict supervision from both internal and external parties is crucial to prevent abuse of power. Gijzeling can only be applied after all other collection efforts have failed and must respect the Taxpayer's rights, applied in a proportional and prudent manner to achieve fiscal justice.